Feeling ‘Right’ When You Feel Accepted: Emotional Acculturation in Daily Life Interactions With Majority Members - Jasini, Alba; De Leersnyder, Jozefien; Mesquita, Batja (Frontiers in Psychology, 2018)
When immigrant minority individuals engage in frequent and positive social contact with majority culture members, their emotions become a better fit with the majority norm; the increased fit is called emotional acculturation. In the current research, we test the prediction that high-quality interactions with majority others, in which minorities feel accepted, increase the likelihood of emotional fit. We also explore whether this prediction holds true for both positive and negative interactions with majority. To test this prediction, we conducted a seven-day daily diary study with minority students in Belgian middle schools (N = 117). Each day, participants reported one positive and one negative interaction at school. They subsequently evaluated each interaction (e.g., felt accepted), assessed their relationship with the interaction partner (e.g., our relationship is important to me), and rated their emotions. Analyses focused on the interactions with Belgian majority interaction partners. Emotional acculturation was computed for positive and negative interactions separately, by calculating the fit between the emotional pattern of the minority student and the average emotional pattern of a sample of majority participants (N = 106) who also took part in the daily diary. As predicted, we found higher emotional fit in positive interactions when immigrant minorities felt accepted by the interaction partner. In contrast to this finding for positive interactions, emotional fit for negative interactions was higher when minorities felt excluded by the interaction partner. Further analyses on the negative interactions suggested that minority adolescents felt more negative autonomy-promoting emotions (e.g., anger and frustration) when they perceived being excluded. Given that Belgian majority youth feel more autonomy-promoting emotions generally, minorities’ fit with majority patterns was higher. The results confirm our hypothesis that minorities’ fit with majority emotions is contingent on the quality of their interactions with majority, even if in negative interactions, high-quality interactions produced less rather than more emotional fit. Our findings suggest that emotional acculturation is not just a ‘skill’ that minority individuals acquire, but also a response to the ways in which interactions with majority others develop. Inclusive interactions, especially when they are positive, appear to align immigrant minority individuals with the majority norm.